THE CROSS IN THE CRESCENT'S EYE : Theology of the Cross in Muslim Context and its Significances for Christian Mission - Notomihardjo, Robbyanto (Jurnal Amanat Agung, 2006)
THE CROSS IN THE CRESCENT'S EYE